Cocaine-induced Movement Disorder: A Literature Review - Byroju, Vishnu Vardhan; Rissardo, Jamir Pitton; Durante, Ícaro; Caprara, Ana Letícia Fornari (Prague medical report, 2024)
This study aims to describe movement disorders secondary to cocaine use. To our knowledge, while these presentations have been previously reported in the literature, a comprehensive review has not been published yet. We searched six databases from 1986 to 2022 without language restriction. Case reports, case series, and literature reviews have been analysed to find associations between cocaine use and movement disorders. The present study encompasses epidemiology, clinical manifestations, pathophysiology, and diagnostic challenges of abnormal movements associated with cocaine use. This review highlights the importance of proper initial evaluation and investigation taking into account the broad spectrum of differential diagnoses and exclusion of primary movement disorders. The role of the dopaminergic system in movement disorders is reviewed. Cocaine use is associated with movement disorders such as dystonia, parkinsonism, akathisia, and tics. The complex interaction of multiple factors, including other neurological conditions, such as Tourette syndrome, and additional substances of abuse is discussed. The presentation of these manifestations is often heterogeneous and does not follow a specific pattern. In this way, future research is needed to improve our understanding of the pathophysiological mechanisms and develop novel drug targets for these disorders. Increased awareness among the general public and policymakers could translate into reduced stigma and improved care.
Keywords: poruchy spojené s užíváním kokainu; Cocaine-Related Disorders; pohybové poruchy; lidé; Movement Disorders; kokain; Cocaine; Humans